Answer :

Let P(n) = = (n+1)

P(1) is true.

Assuming P(k) is true.

P(k) = = K+1

To prove P(k+1) is true.

P(k+1) = = K+2………….(1)

L.H.s of (1)

= (k+1)1+

= = K+2

Which is the R.H.S of (1)

P(K+1) is true.

By the Principle of mathematical induction, P(n) is true for all values of n where n N

Hence proved.

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation